Cuckoo Search Design Optimization and Analysis of Matching Circuits composed of CRLH Transmission Cells - Karataev, T.; Gunes, F.; Demirel, S. (IEEE, 2015)
This paper presents the design optimization and analysis of Matching Circuits (MCs) composed of identical Composite Right/Left-Handed (CRLH) transmission cells in the balanced conditions. For this purpose, noise matching is considered as the Feasible Design Target (FDT) throughout the available bandwidth for a chosen low-noise microwave transistor which is BPF640 and the L, C element values, number of identical asymmetric CRLH TL cells are taken as the optimization variables. This FDT is expressed simply by the two alternative objective functions which are the expressions for the gain and port impedance approaches together with the balanced condition. Furthermore, the effect of transition frequency on the matching vs frequency characteristics is investigated. A novel metaheuristic algorithm Cuckoo Search (CS) combined with the Levy flight is used as a fast and accurate tool to find out the Global Optimum within the Feasible Design Variable Space (FDVS) in the design procedure. The computed results are given in details which are also verified by AWR circuit simulator. It can be concluded that the CRLH transmission cells can be employed in the design of the miniaturized ultra-wide band microwave amplifiers due to their broadband matching capabilities.
Keywords: Matching; Composite Right/Left-Handed Transmission Cell; Optimization; Feasible Design Target; Feasible Design Variables; Computer Science